The Other Lady Vanishes : Burning Cove #2 - Quick, Amanda (New York : Berkley, 2018)
"After escaping from a private sanitarium, Adelaide Blake arrives in Burning Cove, California, desperate to start over. Working at an herbal tea shop puts her on the radar of those who frequent the seaside resort town: Hollywood movers and shakers always in need of hangover cures and tonics. One such customer is Jake Truett, a recently widowed businessman in town for a therapeutic rest. But unbeknownst to Adelaide, his exhaustion is just a cover. In Burning Cove, no one is who they seem. Behind facades of glamour and power hide drug dealers, gangsters, and grifters. Into this make-believe world comes psychic to the stars Madame Zolanda. Adelaide and Jake know better than to fall for her kind of con. But when the medium becomes a victim of her own dire prediction and is killed, they'll be drawn into a murky world of duplicity and misdirection. Neither Adelaide nor Jake can predict that in the shadowy underground they'll find connections to the woman Adelaide used to be--and uncover the specter of a killer who's been real all along.."--.
"After escaping from a private sanitarium, Adelaide Blake arrives in Burning Cove, California, desperate to start over. Working at an herbal tea shop puts her on the radar of those who frequent the seaside resort town: Hollywood movers and shakers always in need of hangover cures and tonics. One such customer is Jake Truett, a recently widowed businessman in town for a therapeutic rest. But unbeknownst to Adelaide, his exhaustion is just a cover. In Burning Cove, no one is who they seem. Behind facades of glamour and power hide drug dealers, gangsters, and grifters. Into this make-believe world comes psychic to the stars Madame Zolanda. Adelaide and Jake know better than to fall for her kind of con. But when the medium becomes a victim of her own dire prediction and is killed, they'll be drawn into a murky world of duplicity and misdirection. Neither Adelaide nor Jake can predict that in the shadowy underground they'll find connections to the woman Adelaide used to be--and uncover the specter of a killer who's been real all along.."--
Keywords: FICTION / Romance / Suspense; Romantic suspense fiction; Mystery fiction